Minimization of CYP2D6 Polymorphic Differences and Improved Bioavailability via Transdermal Administration: Latrepirdine Example - Chew, Marci L.; Mordenti, Joyce; Yeoh, Thean; Ranade, Gautam; Qiu, Ruolun; Fang, Juanzhi; Liang, Yali; Corrigan, Brian (Pharmaceutical research, 2016)
Purpose Transdermal delivery has the potential to offer improved bioavailability by circumventing first-pass gut and hepatic metabolism. This study evaluated the pharmacokinetics of oral immediate release and transdermal latrepirdine in extensive and poor CYP2D6 metabolizers (EM/PM). Methods Latrepirdine transdermal solution was prepared extemporaneously. The solution was applied with occlusive dressing to upper or middle back for 24 h. Each subject received a single dose of 8.14 mg oral, 5 mg transdermal, and 10 mg transdermal (EMs only) latrepirdine free base in a fixed sequence. Results Twelve EMs and 7 PMs (50–79 years) enrolled and completed the study. Latrepirdine was well tolerated following both routes of administration. Dose-normalized latrepirdine total exposures were approximately 11-fold and 1.5-fold higher in EMs and PMs, respectively following administration of transdermal relative to oral. Differences between EM and PM latrepirdine exposures were decreased, with PMs having 1.9- and 2.7-fold higher peak and total exposures, respectively, following transdermal administration compared to 11- and 20-fold higher exposures, respectively, following oral administration. Conclusion Transdermal delivery can potentially mitigate the large intersubject differences observed with compounds metabolized primarily by CYP2D6. Transdermal delivery was readily accomplished in the clinic using an extemporaneously prepared solution [NCT00990613].